Effects of the Enhanced Recovery After Surgery Protocol on Postoperative Recovery, Sleep Quality, and Postpartum Depression in Elective Cesarean Section Patients: A Single-Center, Prospective Study - Keleş Tayfur, Elif; Keskin, Deha Denizhan (The European Research Journal, 2026)
Objective: To assess the effects of the Enhanced Recovery After Surgery–Cesarean Delivery (ERAS-CD) protocol on early postoperative recovery, pain scores, postpartum sleep quality, and postpartum depression in patients undergoing elective cesarean delivery. Methods: This single-center prospective cohort study involved women with at least one cesarean delivery who underwent planned CD between December 2022 and May 2023. The primary outcome was to reduce hospital stay and morbidity following CD. Secondary outcomes included breastfeeding/formula supplementation status, postoperative pain score, postpartum sleep quality, and predisposition to postpartum depression. The protocol included preoperative oral intake of cherry juice, multimodal analgesia, antiemetic medications, and early ambulation. The number of patients and minimum sample size per group were determined based on power analysis results from previous studies. Results: A total of 294 patients were included in the study. The ERAS-CD protocol group and the control group were similar in demographic characteristics, body weight, and parity (P>0.05). Postoperative Visual Analog Scale and severe pain scores were lower in all components of the ERAS-CD protocol group (P<0.001). The total score and two subcomponent scores (Sleep duration and Habitual sleep efficiency) of the Pittsburgh Sleep Quality Index were significantly lower in the ERAS-CD group (P=0.005, P=0.004, and P=0.016; respectively). The total score of the Postoperative Recovery Index, as well as the subcomponent scores for bowel symptoms and general symptoms, were significantly lower in the ERAS-CD group (P=0.041, P=0.020, and P=0.045; respectively). Moreover, the Edinburgh Postnatal Depression Scale score and the score indicating predisposition to depression were significantly lower in the ERAS-CD group (P<0.001 for both). Conclusion: Consistent with the existing literature, the present study demonstrates that the implementation of the ERAS-CD protocol in Cesarean Deliveries has favorable effects on preoperative, intraoperative, and postoperative outcomes. Specifically, the ERAS-CD protocol was shown to reduce postoperative pain, improve postpartum sleep quality, and decrease the predisposition to postpartum depression.